2010
DOI: 10.1111/j.1095-8312.2010.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype diversity of the nematode Pristionchus pacificus on Réunion in the Indian Ocean suggests multiple independent invasions

Abstract: Pristionchus pacificus has been established as a nematode model system in evolutionary developmental biology and evolutionary ecology. Field studies in North and South America, Asia, Africa and Europe indicated that nematodes of the genus Pristionchus live in association with scarab beetles. Here, we describe the first account of soil-and beetle-associated nematodes on an island setting by investigating the island of Réunion in the Indian Ocean. Réunion has high numbers of endemic insects and is one among seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(132 citation statements)
references
References 21 publications
5
126
1
Order By: Relevance
“…Control animals show gonad-independent differentiation in 30-60% of the VPCs according to the RS5275/BOL genetic background. Controls include non-transgenic sisters (*) that have lost the transgenic array of both constructs (8,10), Ppa-egl-20::RFP transgenic animals (11), or RS5275/BOL wild-type animals (12). Error bars denote standard deviation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Control animals show gonad-independent differentiation in 30-60% of the VPCs according to the RS5275/BOL genetic background. Controls include non-transgenic sisters (*) that have lost the transgenic array of both constructs (8,10), Ppa-egl-20::RFP transgenic animals (11), or RS5275/BOL wild-type animals (12). Error bars denote standard deviation.…”
Section: Resultsmentioning
confidence: 99%
“…All strains used in this study were inbred for at least 10 generations and are described elsewhere 10,11 . Cell-ablation experiments were carried out using standard techniques 27 , by ablating the gonad 0-1 h after hatching of the larvae (20°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential support for a role of oxidative stress comes from the known ecosystem of P. pacificus and related nematodes. Unlike C. elegans, Pristionchus lives in tight association with scarab beetles in a necromenic interaction (Herrmann et al 2007(Herrmann et al , 2010. Nematodes rest on the living beetle in the dauer stage (Weller et al 2010) and resume development on the beetle carcass only to feed on all types of microbes (McGaughran et al 2013).…”
Section: Speciesmentioning
confidence: 99%
“…A subset of 104 P. pacificus wild isolates had their genome of 169 Mb resequenced, which revealed strong divergence, resulting in .6 million single-nucleotide polymorphisms (SNPs) (Rödelsperger et al 2014). Furthermore, the patterns of divergence and global dispersal between the four P. pacificus clades and the repeated invasion of the geologically young volcanic island of La Reunion (Herrmann et al 2010;McGaughran et al 2013) indicated that the P. pacificus genome is shaped by weakly deleterious mutations and linked selection (Rödelsperger et al 2014). These studies provide a genomic and phylogenetic framework for evolutionary comparisons of mutational patterns.…”
mentioning
confidence: 99%